Changes in drug handling during pregnancy: What it might mean for your patients - Koren, Gideon (College of Family Physicians of Canada, 2006)
QUESTION: A pregnant patient taking lithium for bipolar depression is clinically uncontrolled despite a high dose. She insists that she is taking the medication. Her lithium serum levels have fallen from 1 mEq/L to 0.6 mEq/L. What is the reason for this change? ANSWER: Lithium is eliminated by the kidney. In late pregnancy the glomerular filtration rate increases substantially and hence elimination of the drug can almost double. Liver biotransformation pathways might also increase the rate of elimination of various drugs, causing lower levels and, potentially, suboptimal therapy.